Bipolar Atlantic deepwater circulation in the middle‐late Eocene: Effects of Southern Ocean gateway openings. (21st April 2014) - Borrelli, Chiara; Cramer, Benjamin S.; Katz, Miriam E.
Abstract We present evidence for Antarctic Circumpolar Current (ACC)‐like effects on Atlantic deepwater circulation beginning in the late‐middle Eocene. Modern ocean circulation is characterized by a thermal differentiation between Southern Ocean and North Atlantic deepwater formation regions. In order to better constrain the timing and nature of the initial thermal differentiation between Northern Component Water (NCW) and Southern Component Water (SCW), we analyze benthic foraminiferal stable isotope (δ18Obf and δ13Cbf) records from Ocean Drilling Program Site 1053 (upper deep water, western North Atlantic). Our data, compared with published records and interpreted in the context of ocean circulation models, indicate that progressive opening of Southern Ocean gateways and initiation of a circum‐Antarctic current caused a transition to a modern‐like deep ocean circulation characterized by thermal differentiation between SCW and NCW beginning 38.5 Ma, in the initial stages of Drake Passage opening. In addition, the relatively low δ18Obf values recorded at Site 1053 show that the cooling trend of the middle‐late Eocene was not global, because it was not recorded in the North Atlantic. The timing of thermal differentiation shows that NCW contributed to ocean circulation by the late‐middle Eocene, 1–4 Myr earlier than previously thought. We propose that early NCW originated in the Labrador Sea, based on tectonic reconstructions and changes in foraminiferal assemblages in this basin. Finally, we link further development of meridional isotopic gradients in the Atlantic and Pacific in the late Eocene with the Tasman Gateway deepening ( 34 Ma) and the consequent development of a circumpolar proto‐ACC.